Acts of tolerance: A political and descriptive account. (July 2014) - Balint, Peter
Almost all philosophical understandings of tolerance as forbearance require that the reasons for objection and/or the reasons for withholding the power to negatively interfere must be of the morally right kind. In this paper, I instead put forward a descriptive account of an act of tolerance and argue that in the political context, at least, it has several important advantages over the standard more moralised accounts. These advantages include that it better addresses instances of intolerance and that it is able to makes sense of state acts of tolerance.